Uterine Artery Doppler Screening in Prediction of Adverse Perinatal Outcome (Delta Medical College Journal, 2025)
Background: Uterine artery Doppler velocimetry (UADV) can detect any pathological increase in placental vascular resistance, and thus can detect women at risk for developing adverse perinatal outcome. Materials and method: This prospective observational study was carried out in the department of Obstetrics and Gyn ecology, BIRDEM General Hospital (Women and Children), Segunbagicha, Dhaka, Bangladesh, from July 2021 to December 2021. A total of 31 women with singleton pregnancy were enrolled in this study at their 18-24 weeks of gestation and uterine artery Doppler velocimetry was done to observe its relationship with adverse perinatal outcome. Data were collected using a semi-structured questionnaire. Relevant statistical analyses were done using SPSS v.21. Results: The mean age was found 29.71±4.8 years with a range from 21 to 40 years. Most (96.8%) of the subjects had diabetes mellitus and only 32.3% had hypertension. Diastolic flow of the uterine arteries was reduced in 45.16% subjects and 32.3% had diastolic notch. Majority (64.3%) of the babies of the respondents with decreased diastolic flow developed fetal growth retardation (FGR) and fetal distress (57.1%) and 85.7% babies needed neonatal intensive care unit (NICU) admission. Majority of the respondents with diastolic notch also developed FGR (60.0%) and 80.0% babies needed NICU admission. All these findings were statistically significant (p